Sexualized Labor, Women’s Respectability and Gender Disparity in Casino Industry of North Cyprus - Aydın, İlkem Aysel (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This is the first research of its type to investigate and describe the female working conditions at TRNC casinos. The study aims to investigate a host community's perception of the social and cultural impacts on female casino employees in Northern Cyprus, gender disparity within the casino organizations, female casino employee’s respectability and also sexual labor. The study also evaluates this perception in the context of the community's concerns about the struggles of women who work in North Cyprus casinos, and it develops information of the respondents in terms of their attitudes toward women who work in the North Cyprus casino industry. We have asked 4 introduction questions to analyze the participants age and other necessary information. Then went into semi structured interviews via internet and we asked 15 questions in total to 20 participants from different casinos located in North Cyprus. Our questions were focused on 3 aspects: Sexualized labor, women’s respectability, and gender disparity. After analyzing the study findings, we drew conclusions. According to the findings, women working in the Northern Cyprus casino industry encounter several challenges. Sexualized work, gender disparity, and their respectability are at the heart of these issues. Keywords: Women Employee, Casino, Tourism Development; Feminism, North Cyprus.

ÖZ: Bu çalışma, KKTC casino sektörünün kadınlar için çalışma koşullarını araştıran ve tanımlayan KKTC’de türünün ilki bir araştırmasıdır. Çalışma, araştırmaya ev sahibi olan Kuzey Kıbrıs'taki kadın casino çalışanları üzerindeki sosyal ve kültürel etkileri, casino organizasyonlarındaki cinsiyet eşitsizliğini, kadın casino çalışanlarının saygınlığını ve ayrıca cinsel emeği araştırmayı amaçlamaktadır. Çalışma ayrıca toplumun Kuzey Kıbrıs casinolarında çalışan kadınların mücadelelerine ilişkin kaygıları bağlamında da değerlendirmekte ve toplumun Kuzey Kıbrıs casino endüstrisinde çalışan kadınlara yönelik tutumları açısından da bilgi havuzu geliştirmektedir. Çalışmamızda öncelikle katılımcının yaşını ve diğer gerekli bilgileri analiz etmek için 4 giriş sorusu sorduk. Daha sonra internet üzerinden yarı yapılandırılmış görüşmelere geçilerek Kuzey Kıbrıs'ta bulunan farklı casinolardan 20 katılımcıya toplam 15 soru yönelttik. Sorularımız 3 konuya odaklanmıştır: Cinselleştirilmiş emek, kadınların saygınlığı ve cinsiyet eşitsizliği. Çalışma bulgularını analiz ettikten sonra, sonuçlar çıkarıldı. Bulgulara göre, Kuzey Kıbrıs casino endüstrisinde çalışan kadınlar çeşitli zorluklarla karşılaşmaktadır. Cinselleştirilmiş emek, cinsiyet eşitsizliği ve saygınlıkları bu konuların merkezinde yer almaktadır. Anahtar Kelimeler: Kadın Çalışanlar, Casino, Turizm Geliştirme; Feminizm, Kuzey Kıbrıs.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2022. Supervisor: Asst. Prof. Dr. İlkay Yorgancı Maloney.
Keywords: Tourism Faculty; Tourism - Casino Industry; Gender Disparity - Women; Employee - Cyprus (Turkish Republic of Northern Cyprus, 1983-); Women Employee - Work Concitions - Casinos - Cyprus (Turkish Republic of Northern Cyprus, 1983-); Women - labor economics; Women - Employment; Women - Social conditions; Women Employee, Casino, Tourism Development; Feminism, North Cyprus